1993
DOI: 10.1136/pgmj.69.807.45
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and nosocomial acquisition of Clostridium difficile in elderly hospitalized patients

Abstract: Summary:Rectal swabs obtained from 10 of 49 chronic-care geriatric patients were positive for Clostridium difficile, for a prevalence rate of 20.4%. Simultaneous sampling of 29 patients in an acute geriatric ward revealed four colonized patients, for a prevalence rate of 13.7%.A prospective study of C. difficile colonization in 100 consecutive patients admitted to an acute geriatric ward was carried out. All patients were sampled upon admission and biweekly during hospitalization. Two patients (2%) were positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
2
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 13 publications
1
18
2
3
Order By: Relevance
“…CDAD is reportedly more common among older individuals (6,10,20,21,(24)(25)(26). In this study, 176 patients (67%) were older than age 65 years; this high proportion of older patients may reflect that there are larger numbers of elderly hospitalized patients or that older individuals are more susceptible to C difficile infections.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…CDAD is reportedly more common among older individuals (6,10,20,21,(24)(25)(26). In this study, 176 patients (67%) were older than age 65 years; this high proportion of older patients may reflect that there are larger numbers of elderly hospitalized patients or that older individuals are more susceptible to C difficile infections.…”
Section: Discussionmentioning
confidence: 84%
“…LOS in hospital has been found to be significant in determining whether patients become colonized, and subsequently symptomatic, with C difficile (20). People with a longer LOS are generally older, sicker and on antibiotics, which may render them more susceptible to acquiring C difficile colonization or infection (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have, in the recent past, encountered a relatively high proportion of asymptomatic carriers of C. difficile in our hospitals, and the interpretation of positive cultures was equivocal. C. difficile or its toxin has been reported in one study from nearby Saudi Arabia (Akhter et al, 1994), in Turkey (Soyletir et al, 1996) and in a few reports from Israel (Rudensky et al, 1993;Rivlin et al, 1998;Boaz et al, 2000). However, this is the first report on PCR ribotyping of C. difficile strains isolated from symptomatic and asymptomatic patients in the Middle East.…”
mentioning
confidence: 99%
“…The analysis of epidemiological studies showed that there was a difference in the rate of carriership depending on the patient type. Asymptomatic carriership was found in 7% of patients hospitalized for a long time in a general ward [13], 14% of elderly patients hospitalized in the intensive care unit [14] and 20% of elderly patients hospitalized for chronic illnesses and in need of other care and assistance or for the maintenance of vital functions [15]. Some studies indicated that among hospitalized patients older than 65 years, the rate of carriership was even up to 30% [4,5].…”
Section: Discussionmentioning
confidence: 99%